2016
DOI: 10.4253/wjge.v8.i20.756
|View full text |Cite
|
Sign up to set email alerts
|

Clinical problems with antithrombotic therapy for endoscopic submucosal dissection for gastric neoplasms

Abstract: Endoscopic submucosal dissection (ESD) is minimally invasive and thus has become a widely accepted treatment for gastric neoplasms, particularly for patients with comorbidities. Antithrombotic agents are used to prevent thrombotic events in patients with comorbidities such as cardio-cerebrovascular diseases and atrial fibrillation. With appropriate cessation, antithrombotic therapy does not increase delayed bleeding in low thrombosis-risk patients. However, high thrombosis-risk patients are often treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
(80 reference statements)
0
9
0
1
Order By: Relevance
“…We had 16 patients on warfarin in whom we carried out ESD without HBT. All of them, including eight patients with AF with a CHADS 2 score of 0–1 and two patients with deep vein thrombosis, were decided by the prescribing doctors for their low thrombotic risk, although recent Japanese guidelines recommend HBT to all patients on warfarin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had 16 patients on warfarin in whom we carried out ESD without HBT. All of them, including eight patients with AF with a CHADS 2 score of 0–1 and two patients with deep vein thrombosis, were decided by the prescribing doctors for their low thrombotic risk, although recent Japanese guidelines recommend HBT to all patients on warfarin.…”
Section: Resultsmentioning
confidence: 99%
“…Still, bleeding risk for antiplatelet agents is manageable in most cases. Aspirin is the most popular antiplatelet agent and is reported not to increase delayed bleeding risk if aspirin is continued during the perioperative period of ESD However, managing delayed bleeding risk in anticoagulants is difficult . When we discontinue warfarin, heparin bridge therapy (HBT) is usually required to prevent thrombotic events .…”
Section: Introductionmentioning
confidence: 99%
“…The American Society for Gastrointestinal Endoscopy (ASGE) guidelines and JGES guidelines published in 2012 recommend bridge therapy for patients using VKAs before undergoing high risk endoscopic procedures in those who are at high risk for the development of thromboembolic events 5 9 . However, previous studies by our own group have shown a high risk of gastrointestinal bleeding after HB 12 13 28 . Similar to these retrospective studies, our prospective study confirmed a higher risk of post-procedural gastrointestinal bleeding in patients using VKAs who received HB than in those who did not receive HB.…”
Section: Discussionmentioning
confidence: 75%
“…The incidence rates of thrombotic events related to endoscopic surgery were 0–4.2% [18, 19]. In addition, the interruption of warfarin for 4 to 7 days induced thromboembolic events in approximately 1% of patients [20].…”
Section: Discussionmentioning
confidence: 99%